Immune modulation following α and β− radionuclide therapy targeting fibroblast activation protein-α in a preclinical tumor model - Hannelore Ceuppens; Kirsten De Ridder; Thomas Ertveldt; Katty Zeven; Wout De Mey; Ana Rita Pombo Antunes; Laurent Navarro; Nina Dumauthioz; Tony Lahoutte; Jens M. Debacker; Nick Devoogdt; Marleen Keyaerts; et al. (OncoImmunology, 2025)
α- and β−-emitting radionuclides targeting human fibroblast activation protein-α (hFAP) are under investigation for cancer therapy. In prior work, analysis of the tumor microenvironment 24 h after therapy completion indicated therapy-induced immune activation. Here, we analyzed systemic immune responses at varying timepoints during treatment to further elucidate the immune-stimulating effects of the therapy. Moreover, we analyzed end-stage tumors to gain insight in potential mechanisms of therapy resistance. Single domain antibody 4AH29 that binds hFAP was labeled with 131I or 225Ac, generating [131I]I-GMIB-4AH29 and [225Ac]Ac-DOTA-4AH29, respectively. These were used to treat C57BL/6 mice bearing subcutaneous TC-1-hFAP tumors. Blood analysis was conducted using flow cytometry, while tumor characterization was performed using flow cytometry and RNA sequencing. Given the distinct properties and doses of both radiopharmaceuticals, no head-to-head comparison was performed. Both treatments activated inflammatory responses in the tumor. Increased PD-1 expression on CD8+ T-cells was observed following both treatments in the tumor and periphery. In the tumor, [131I]I-GMIB-4AH29 therapy uniquely induced the expression of genes involved in tumor cell replication, TNF-α, IL-6/STAT3, IL-2/STAT5 and complement pathways, while in the blood [131I]I-GMIB-4AH29 therapy upregulated SIRPα on monocytes and TIGIT on NK cells, and downregulated CD86 expression on monocytes. Longitudinal blood immune cell analysis showed changes in composition and phenotype early in therapy, e.g. in effector and regulatory T-cells. Overall, this study corroborates the immune sensitizing capacity of α- and β−-emitting radionuclides, triggering a variety of inflammatory effector responses.